PENGARUH KUALITAS PRODUK, HARGA, DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN STICK (KARICA) RAJUNGAN UD DIANA DESA KERTASADA KECAMATAN KALIANGET KABUPATEN SUMENEP - Tegar Dwi Yanto; Rusnani Rusnani (Journal MISSY (Management and Business Strategy), 2026)
This study examines the influence of product quality, pricing, and social media on the purchase decisions of Karica crab stick products at UD Diana, located in Kertasada Village, Kalianget District, Sumenep Regency. The purpose of this research is to determine the extent to which product quality, price, and social media individually and simultaneously affect consumer purchasing decisions. This research uses a quantitative approach by distributing questionnaires to 105 respondents who are regular consumers of UD Diana. The sampling technique used is non probability sampling, with respondents required to be at least 17 years old and have purchased the product at least three times. Data were analyzed using multiple linear regression with IBM SPSS Statistics 25 software. The partial test (t-test) results show that: 1) product quality has a significant influence on purchase decisions, 2) price has a significant negative influence, and 3) social media also significantly affects consumer decisions. Meanwhile, the simultaneous test (F-test) confirms that these three variables collectively have a significant impact. The coefficient of determination indicates that 18.3% of the variation in purchasing decisions can be explained by the independent variables in this study.